Status Badan Hukum Perseroan Perorangan Ditinjau dari Hukum Perusahaan Indonesia - Rizky Yonanda; Zahara Zahara; Shafira Hijriya (Lareh Law Review, 2023)
Limited Liability Company (LLC) is a legal entity that was born based on an agreement, this has been in effect since the KUHD era to Law Number 40 of 2007 concerning LLC. This concept then underwent a change after the enactment of Law Number 11 of 2020 concerning Cipta Kerja which introduced a new model of LLC, namely an Single Member Limited Liability Company (SMLLC) which is intended for businesses that meet the criteria as Micro and Small Enterprises (UMK). This is contradictory to the principle of a legal entity which requires the legal entity to be a place where people gather to achieve collective goals; and contrary to the prevailing doctrines in legal entities so far. Based on this, this study aims to discuss the legal status of SMLLC and the consequences for the separate entity doctrine by using a normative-juridical research typology. The legal status of an individual company has fulfilled the formal requirements as a legal entity, namely the existence of approval by the state. However, materially SMLLC does not automatically fulfill the four other legal entity requirements, namely the existence of assets entity separation, a specific purpose, self-interest, and organ structure, so that an SMLLC doesn’t meet the requirements as a legal entity. Then,  the personality of the founder also cannot be separated from the personality of the legal entity. This is linear with the increasingly dominant role of the piercing the corporate veil doctrine, and reducing the role of the separate entity doctrine itself